2020 한국인 영양소 섭취기준 활용 자료를 이용한 영양교육 프로그램의 적용 및 효과: 경상남도 및 경기도 지역 대학생을 대상으로 - 최미주(Mijoo Choi); 정혜인(Hyein Jung); 김나영(Nayoung Kim); 신상아(Sangah Shin); 우태정(Taejung Woo); 박은주(Eunju Park) (Journal of nutrition and health, 2023)
Purpose: The 2020 Dietary Reference Intakes for Koreans (KDRIs) serves as a foundation for daily nutrient and energy recommendations aiming to enhance public health and prevent chronic diseases. They act as guidelines for maintaining proper nutrition and overall health. Using KDRIs is crucial for promoting healthier lifestyles and making informed dietary choices. Thus, this study explores the influence of a nutrition education program, based on the 2020 KDRIs, on the nutrition knowledge and dietary habits of undergraduates in Gyeongsangnam-do and Gyeonggi-do. Methods: The nutrition education program, designed with diverse instructional materials, was executed across a wide range of universities. The education group (n = 75) engaged in the program for a 6-week instructional period, while the control group (n = 53) underwent the survey without participating in the education program. Nutrition Quotient (NQ) and knowledge assessments were administered to both groups immediately before and after the instructional period. Results: Within the education group, the nutrition education program positively impacted responses to NQ practice items, including knowledge of nutrition, daily intake, and portion sizes (p < 0.05). In contrast, there were no significant differences between the before and after responses of the control group for most survey items. Post-program evaluations showed significantly higher self-assessment scores and increased satisfaction levels (p < 0.05), with the satisfaction rate for the education program using the 2020 KDRIs reaching 99.2%. Conclusion: This study has demonstrated the positive impact of an effective nutrition education program. However, there is a need for the continuous development and implementation of nutrition education programs to sustain these outcomes and further enhance the nutritional education experience. 본 연구는 2020 KDRIs를 활용한 영양 교육 프로그램 및 교육매체가 대학생의 영양 지식과 식습관에 미치는 영향을 조사하였다. 다양한 교육매체 (테이블 매트, 레시피북 등)를 바탕으로 설계된 교육 프로그램은 경상남도 및 경기도 지역의 대학에서 시행되었다. 본 연구에 참여한 대상자는 총 128명이이었으며, 교육군 (n = 75)과 대조군 (n = 53)은 무작위 배정하였다. 교육군은 교육 프로그램 참여 전에 영양 지수 (NQ) 및 영양지식 평가 설문지 조사를 실시하였으며, 6주간의 교육 기간 동안 교육 프로그램 참여 후 동일한 설문지를 이용하여 영양 지수 (NQ) 및 지식 평가를 진행하였다. 대조군은 6주간의 교육 프로그램 참여없이 사전 및 사후에 영양지수 (NQ) 및 영양지식 평가 설문지 조사만 참여하였다. 교육군은 6주간의 2020 KDRIs를 활용한 영양 교육 프로그램의 영향으로 NQ 실천 항목, 영양 지식, 1일 섭취량 및 식사량 지식 (p < 0.05)에 대한 응답에서 긍정적인 결과를 나타냈다. 또한 프로그램 참여 후 최종평가 결과에서 자기평가 점수가 유의하게 높게 나타났으며, 자기만족도는 증가한 것으로 나타났고 (p < 0.05), 2020 KDRIs를 활용한 영양 교육 프로그램에 대한 전체적인 만족도는 99.2%를 달성했다 (p < 0.000). 그러나 대조군의 경우에는 큰 변화를 확인할 수 없었다. 따라서, 본 연구는 2020 KDRIs를 활용한 영양 교육 프로그램 및 교육 매체가 대학생의 영양지식과 식습관에 긍정적인 영향을 미친다는 것을 입증했다. 그러나 이러한 결과를 유지하고 꾸준히 실천하기 위해서는 다양한 영양 교육 프로그램의 지속적인 개발과 실행이 필요할 것이다.